THE INFLUENCE OF HEAT TREATMENT ON MICROSTRUCTURE AND CORROSION RESISTANCE OF 13Cr-1Mo MARTENSITIC STAINLESS STEEL - Siska Prifiharni; Moch. Syaeful Anwar; Efendi Mabruri (Widyariset, 2016)
Martensitic stainless steels have been extensively used for a turbine blade. Their properties can be improved in various ways, such as by heat  treatment. This paper aims to investigate the influence of heat treatment on microstructure and corrosion resistance in martensitic stainless steel 13Cr-1Mo. Samples were austenitized at 950 ºC, 1.000 ºC, 1.050 ºC, 1.100 ºC, and tempered at 600 ºC. Austenitized sample at 1.050 ºC was subsequently tempered at 300 ºC, 400 ºC, 500 ºC, 550 ºC, 600 ºC, 650 ºC, and 700 ºC. The tests consist of metallographic observation which was conducted by using an optical microscope and corrosion tests which were conducted by using 3,5% NaCl solution. The results show the evolution of microstructure in martensitic stainless steel 13Cr-1Mo after heat treatment. The microstructure formed consists of tempered martensite, delta ferrite, retained austenite, and carbides. The presence of carbides can also affect corrosion resistance, which will increase along with the increase of tempering temperature due to the increased content of Cr in the carbides. The highest value corrosion resistance was obtained at the austenitizing temperature of 1.050 ºC and tempering temperature of 600 ºC.